PENGARUH KOMPENSASI TERDAHAP MOTIVASI KERJA PEGAWAI SAAT PANDEMI COVID-19 DI KANTOR KECAMATAN SERANG PANJANG SUBANG - Setiani, Andini; Wardiani, Anita; Fatihah, Dian Candra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This observation intends to describe the effect of compensation on employee work motivation during the covid-19 pandemic in the Serangpanjang Subang District Office. The process in this research uses descriptive quantitative methods conducted through the collection of questionnaire data, and literature studies that have a close correlation classifying variable X and variable Y. The primary data in this study was obtained from a questionnaire whose assessment using the Likert scale was then completed statistically through the SPSS program version 26.0. Based on the assessment that has been conducted, obtained factual conclusions compensation for employee motivation has a large influence on the motivation of employees, this is known from the correlation coeffesien point of 0.624 (62.4%) which is at the interval of relationship level with strong categories. Then the results of the T hypothesis test stated that there was a compensatory influence on employee work motivation, namely the gain of a value of 4,370 Lebih dari 1,697 (thitung lebih dari ttabel), thus Ho was eliminated and Ha was recognized which means there is a considerable influence among compensation on employee work motivation, in addition to the determination of 0.389 thus compensation affects the performance of its employees by 38.9% while the rest is influenced by other factors. The advice that can be put forward is that the company should use this research as a thought material to improve compensation well and guide or give directions to employees